Increasing Hermaphrodite Flowers using Plant Growth Regulators in Andromonoecious Jatropha curcas - . DASUMIATI; . MIFTAHUDIN; . TRIADIATI; ALEX HARTANA; DIBYO PRONOWO (Bogor Agricultural University, Indonesia, 2014)
Jatropha curcas (JC) is a crop with potential for use in biodiesel. Production of biodiesel requires plant seed as raw material, so the viability of JC for use in biodiesel will dependent greatly on the plant’s production of flowers. Generally, this plant is monoecious, meaning it has both male and female flowers. However, very rarely JC plants may be andromonoecious. Andromonoecious specimens of JC produce hermaphrodite and male flowers in the same plant. The number of hermaphrodite flowers per inflorescence is generally low compared to the number of male flowers. The aim of this study was to increase the proportion of hermaphrodite flowers by using plant growth regulators (PGRs) in andromonoecious JC. Our experiment was conducted in Randomized Block Design (RBD) with 9 treatments, namely kinetin, GA3, and IAA with concentrations of 0 ppm as a control, 50 and 100 ppm of each PGRs. The treatments were applied to stem cuttings from each plant and repeated 4 times. PGRs were applied by spraying the leaves within the buds of each plant. Applications took place weekly beginning when the plants entered flower initiating phase, until inflorescence produced. Observations were conducted during the treatment period (10 weeks). Results showed that plants treated with IAA, GA3, and kinetin at 50 and 100 ppm produced increased inflorescence per plant. The increases measured were 155.4 and 92.9% of (IAA), 120.4 and 151% (GA3), 96.6 and 51.7% (kinetin) respectively. In addition we found that application and GA3 at concentrations of 50 and 100 ppm, and kinetin at 50 ppm, increased the number of hermaphrodite flowers per inflorescence by 50%, and increased the number of hermaphrodite flowers per plant by 275.6 and 183.1% (IAA), 219.5 and 254.1% (GA3), 162.9 and 103.1% (kinetin) respectively. As would be expected, the number of fruit per plant increased in those specimens treated with IAA, GA3, and kinetin at 50 and 100 ppm. The increases measured were 301.7 and 167.4% (IAA), 211.7 and 257.0% (GA3), 162.5 and 101.4% (kinetin) respectively.